The Effect of Organizational Commitment on Employee Performance with Work Ethics as Moderation Variable - Yuvaidah, Sefina; Asfiyah, Nurul; Febriani, Rizki (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The purpose of this research is to examine the effect of organizational commitment on employee performance with work ethics as moderation variable. This research was conducted on Bankaltimtara Balikpapan employees with a total of 40 respondents. The sampling technique used in this research is the total sampling technique. Using a quantitative approach. Regression analysis and the SPSS 25 program are used as the data analysis technique. The results of this study showed that organizational commitment has a very high scale range, work ethic has a very high scale range, and employee performance has a high scale range. The results showed that there was no significant influence between organizational commitment on employee performance. Work ethic is able to moderate the effect of organizational commitment on employee performance.